Improving Crowdsourcing-Based Image Classification Through Expanded Input Elicitation and Machine Learning - Yasmin, Romena; Hassan, Md Mahmudulla; Grassel, Joshua T.; Bhogaraju, Harika; Escobedo, Adolfo R.; Fuentes, Olac (Frontiers in Artificial Intelligence, 2022)
This work investigates how different forms of input elicitation obtained from crowdsourcing can be utilized to improve the quality of inferred labels for image classification tasks, where an image must be labeled as either positive or negative depending on the presence/absence of a specified object. Five types of input elicitation methods are tested: binary classification (positive or negative); the (x,y)-coordinate of the position participants believe a target object is located; level of confidence in binary response (on a scale from 0-100%); what participants believe the majority of the other participants' binary classification is; and participant's perceived difficulty level of the task (on a discrete scale). We design two crowdsourcing studies to test the performance of a variety of input elicitation methods and utilize data from over 300 participants. Various existing voting and machine learning (ML) methods are applied to make the best use of these inputs. In an effort to assess their performance on classification tasks of varying difficulty, a systematic synthetic image generation process is developed. Each generated image combines items from the MPEG-7 Core Experiment CE-Shape-1 Test Set into a single image using multiple parameters (e.g., density, transparency, etc.) and may or may not contain a target object. The difficulty of these images is validated by the performance of an automated image classification method. Experiment results suggest that more accurate classifications can be achieved with smaller training datasets when the average of the self-reported confidence values is used as an additional attribute for ML algorithms. Moreover, when a relatively larger properly annotated dataset is available, in some cases augmenting these ML algorithms with the results from an automated classifier can achieve even higher performance than what can be obtained by using any one of the individual classifiers. Lastly, supplementary analysis of the collected data demonstrates that other performance metrics of interest, namely reduced false-negative rates, can be prioritized through special modifications of the proposed aggregation methods.